Sosialisasi Kelayakan Aspek Keuangan Pembuatan Briket pada UMKM Produksi Arang di Desa Waringinkaya - Nur Ardiansyah, Hendri; Nasihin, Ihsan; Fatihah, Dhea Imroatul; Hidayat, Samsul (CV. Creative Tugu Pena, 2023)
Waringinkarya is one of the villages located in the Lemah Abang subdistrict of Karawang Regency. Waringinkarya Village is known for its extensive potential in rice farming areas. Based on the livelihood aspect of the village's population, it is quite diverse, with the majority engaged in farming. The processing of agricultural waste such as rice shells into charcoal briquettes holds high economic value and can serve as an alternative to enhance the economic well-being of the village residents. The focus of this project is a UMKM engaged in charcoal production. The main objective of the project is to promote the utilization of agricultural waste in the production of high-value charcoal briquettes. The results of the service project include providing information on production methods and financial projections obtained from the processing of agricultural waste into briquettes. Keywords: Waste, Agriculture, Briquette, UMKM, Financial